Case Study on the Current Status and Existing Issues of Japanese Language Courses for Minor Languages in Wenzhou City - Hui, Xu; Geyu, Chang; A, Dhanalakshmi (International Journal of Engineering and Management Research, 2025)
The article takes schools in Wenzhou that offer Japanese language courses for the college entrance examination as an example. Based on the analysis of the current situation of Japanese language teaching in Wenzhou's college entrance examination, the article uses a case study to analyze the existing problems in Wenzhou's Japanese language teaching for the college entrance examination. It proposes suggestions such as arranging Japanese class time reasonably, improving Japanese language teaching teacher resources, addressing students' own problems, improving teacher-student communication, guiding and encouraging students to learn independently, and enhancing students' confidence in learning.